2020
DOI: 10.31234/osf.io/8kn5f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Acceptance of COVID-19 Vaccines: Cross-National Evidence on Levels and Individual-Level Predictors Using Observational Data

Abstract: The management of the COVID-19 pandemic critically hinges on the approval of safe and effective vaccines but, equally importantly, on high willingness among lay people to use vaccines when approved. To facilitate vaccination willingness via effective health communication, it is key to understand both levels of skepticism towards an approved COVID-19 vaccine and the demographic, psychological and political sources of this skepticism. To this end, we examine the levels and predictors of willingness to use an app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 13 publications
7
60
2
3
Order By: Relevance
“…Scholars have demonstrated that those believing in COVID-19 conspiracies were less likely to engage in social distancing, increased handwashing, mask wearing, and other public health recommended behaviors 4,5,6,7 . Additionally, people holding these beliefs are more likely to reject the COVID-19 vaccine, which is consistent with general work on conspiracy theories and vaccine intention 1,5,8,9,10 . Finally, they might have consequences beyond the realm of public health, as these beliefs might also fuel racially-charged attacks against Asian Americans 2,11 .…”
Section: Mainsupporting
confidence: 83%
“…Scholars have demonstrated that those believing in COVID-19 conspiracies were less likely to engage in social distancing, increased handwashing, mask wearing, and other public health recommended behaviors 4,5,6,7 . Additionally, people holding these beliefs are more likely to reject the COVID-19 vaccine, which is consistent with general work on conspiracy theories and vaccine intention 1,5,8,9,10 . Finally, they might have consequences beyond the realm of public health, as these beliefs might also fuel racially-charged attacks against Asian Americans 2,11 .…”
Section: Mainsupporting
confidence: 83%
“…In terms of sample size, this survey is the biggest national study on attitude towards vaccination carried out in any European state to date [ 4 ]. Among all respondents, 59% answered that they will definitely or probably get vaccinated, which is about the same as in the USA in November 2020 (60%) [ 11 ], lower than China (91%), Australia (85%) and most Western and Northern European countries [ 4 , 12 , 13 , 14 ] but higher than most Eastern and South-Eastern European countries [ 4 ]. However, it should be noted that most of the surveys had been conducted in spring 2020 and the attitudes have probably changed since then.…”
Section: Discussionmentioning
confidence: 99%
“…First, early testing availability was limited, introducing selection bias and higher initial hospitalization rates. We now understand there exists widespread infection amongst asymptomatic and minimally symptomatic individuals [28] . Unfortunately, by the time these data were recognized and well understood, the trial was already well underway.…”
Section: Discussionmentioning
confidence: 99%